Personality and Conflict Analysis of Katniss in the Hunger Games Novel - Mahfudhotin Qomariyah; Ria Kamilah Agustina (Bilingua, 2023)
The purpose of this study is to analyze personality psychology experienced by the main character and also to find out how the conflict that occurs to the main character. The research method used in this study was library research. The data source was the novel “The Hunger Games” by Suzzane Chollins. The data collection techniques used was observation, documentation and note taking. The data analysis used was reading, summarizing, extracting and analyzing. The result of the study can be formulated that there are several conflicts that occur in the main character. The researcher also analyzed the personality of Katniss was described as a brave, loving and unyielding child.